Grain size dependence of hardness in nanocrystalline silicon carbide. Issue 13 (October 2020) - Pan, Chenglong; Zhang, Limin; Jiang, Weilin; Setyawan, Wahyu; Chen, Liang; Li, Zhiming; Liu, Ning; Wang, Tieshan
Highlights: The hardness of nanocrystalline SiC exhibits an inverse Hall-Petch relationship, which is proportional to the fraction of grain interior atoms. The dislocation activities in nanocrystalline SiC are strongly suppressed by grain boundaries. The indentation-induced amorphization of the nanograins occurs preferentially at grain boundaries and the dislocation region in the grains.. Abstract: The response of nanocrystalline silicon carbide (nc-SiC) to nanoindentation is investigated using molecular dynamics (MD) simulation. It is found that the hardness of the nc-SiC decreases with decreasing grain size, showing an inverse Hall-Petch relationship. The behavior is primarily attributed to the reduced number of intact covalent bonds with grain refinement. Dislocation nucleation and growth in nc-SiC are strongly suppressed by the grain boundaries (GBs). In addition to the dislocation region in the grains, the indentation-induced amorphization of nanograins proceeds preferentially from the GBs, leading to grain shrinkage until the grains are fully amorphized. The results provide an improved understanding of the mechanical properties in nc-SiC and other nanostructured covalent materials.